Pola Pembinaan Karakter Anak Remaja Dalam Mengatasi Dampak Nomophobia Gedget Terhadap Kehidupan Sosial, Di Gki Kasih Perumnas, Kota Sorong - Natasya Virginia Leuwol; Lindi Samangun; Burhanuddin Ghazali; Jenny Syafu; Sinthike Sauyai (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The influence of rapid developments in technology and information, one of which is through the use of Gadgets (smartphones). The use of gadgets by children and adolescents at GKI Kasih Perumnas has a negative impact, namely reducing concentration power and increasing the dependence of children and adolescents to be able to do various things that they should be able to do on their own. Activities and patterns of daily behavior of children and adolescents change, such as loss of attention. In real life, because they tend to focus on virtual life and often communicate through social media accounts compared to direct communication in the midst of a social environment, children and adolescents become private individuals, interfere with the health of the brain, eyes, and hands, suffer from insomnia, exhibit, violent behavior, fade creativity, are exposed to the threat of cyberbullying, and have access to gadgets that display all things that children and adolescents should not see yet. Addiction to the excessive use of Gadgets has a health impact on children and adolescents, which is known as nomophobia. If this dependence is not addressed properly, it will cause problems, especially in terms of the development of character education for children and adolescents in a social environment. The research method used is a qualitative method by distributing questionnaires so that it can be seen how much influence the use of gadgets has on children and adolescents in the GKI Kaih Perumnas congregation. Approximately 80% of children and adolescents do not ignore the surrounding social environment, even though they are using gadgets. It can be concluded that there are still many teenagers who care about their surroundings. However, currently, many children and adolescents do not understand how and when gadgets are used properly. Restrictions and directions are needed from within each device while using it.